Status Keperdataan dan Hak Waris Anak Hasil Sewa Rahim dalam Perspektif Hukum Islam dan Undang-Undang Perkawinan - Subairi Subairi (Pustaka Peradaban, 2025)
The development of assisted reproductive technology, particularly the practice of surrogacy, presents new challenges for the Indonesian legal system, especially in determining the civil status and inheritance rights of children born through such mechanisms. To date, Indonesia lacks specific regulations governing surrogacy, leaving the determination of lineage (nasab), the validity of civil relationships, and the protection of children's inheritance rights in a legal gray area. From an Islamic law perspective, the determination of lineage and inheritance rights relies heavily on the principle of al-walad lil-firāsy and maternal provisions that identify the mother as the woman who gives birth. Meanwhile, positive law through the Marriage Law and population administration regulations emphasizes the importance of clarity in parental status within state administrative documents. The inconsistency between these two legal regimes creates fundamental issues when children born through surrogacy do not automatically obtain lineage and inheritance rights from the commissioning parents, while surrogate mothers do not always maintain the expected social or legal relationship as parents. This study is a library research utilizing normative-judicial and comparative approaches, analyzing classical and contemporary fiqh literature, national regulations, and research findings from the last five years regarding surrogacy. The study indicates that uncertainty in determining a child's civil status has direct implications for the limitation of inheritance rights, particularly when conflicts arise between fiqh provisions on lineage and the principles of population administration in positive law. This research proposes a model of legal reconstruction based on child protection and maqāṣid al-syarī‘ah to bridge this dualism, thereby creating legal certainty that is just, comprehensive, and responsive to developments in reproductive technology. Perkembangan teknologi reproduksi berbantu, khususnya praktik sewa rahim (surrogacy), menghadirkan tantangan baru bagi sistem hukum Indonesia, terutama dalam penentuan status keperdataan dan hak waris anak yang dilahirkan melalui mekanisme tersebut. Hingga saat ini, Indonesia belum memiliki regulasi khusus yang mengatur surrogacy, sehingga penetapan nasab, keabsahan hubungan keperdataan, serta perlindungan hak waris anak sering berada dalam ruang abu-abu hukum. Dalam perspektif hukum Islam, penetapan nasab dan hak waris sangat bergantung pada prinsip al-walad lil-firāsy dan ketentuan keibuan yang menetapkan ibu sebagai perempuan yang melahirkan. Sementara itu, hukum positif melalui Undang-Undang Perkawinan dan peraturan kependudukan menekankan pentingnya kejelasan status orang tua dalam dokumen administrasi negara. Ketidaksinkronan kedua rezim hukum tersebut menimbulkan persoalan mendasar ketika anak hasil sewa rahim tidak secara otomatis memperoleh hak nasab dan waris dari pasangan pemesan, sementara ibu pengganti tidak selalu memiliki hubungan sosial maupun legal yang diharapkan sebagai orang tua. Penelitian ini merupakan library research dengan pendekatan yuridis-normatif dan komparatif yang menganalisis literatur fikih klasik–kontemporer, regulasi nasional, serta hasil penelitian lima tahun terakhir terkait surrogacy. Kajian menunjukkan bahwa ketidakpastian penetapan status keperdataan anak berimplikasi langsung terhadap pembatasan hak waris, terutama ketika terjadi pertentangan antara ketentuan fikih tentang nasab dan prinsip administrasi kependudukan dalam hukum positif. Penelitian ini menawarkan model rekonstruksi hukum berbasis perlindungan anak dan maqāṣid al-syarī‘ah untuk menjembatani dualisme tersebut, sehingga tercipta kepastian hukum yang adil, komprehensif, dan responsif terhadap perkembangan teknologi reproduksi.